Carbon Disulfide (CS) Interference in Glucose Metabolism from Unconventional Oil and Gas Extraction and Processing Emissions - Alisa L. Rich; Jay T. Patel; Samiah S. Al-Angari (SAGE Publishing, 2016)
Carbon disulfide (CS 2 ) has been historically associated with the manufacturing of rayon, cellophane, and carbon tetrachloride production. This study is one of the first to identify elevated atmospheric levels of CS 2 above national background levels and its mechanisms to dysregulate normal glucose metabolism. Interference in glucose metabolism can indirectly cause other complications (diabetes, neurodegenerative disease, and retinopathy), which may be preventable if proper precautions are taken. Rich et al found CS 2 and 12 associated sulfide compounds present in the atmosphere in residential areas where unconventional shale oil and gas extraction and processing operations were occurring. Ambient atmospheric concentrations of CS 2 ranged from 0.7 parts per billion by volume (ppbv) to 103 ppbv over a continuous 24-hour monitoring period. One-hour ambient atmospheric concentrations ranged from 3.4 ppbv to 504.6 ppbv. Using the U.S. Environmental Protection Agency Urban Air Toxic Monitoring Program study as a baseline comparison for atmospheric CS 2 concentrations found in this study, it was determined that CS 2 atmospheric levels were consistently elevated in areas where unconventional oil and gas extraction and processing occurred. The mechanisms by which CS 2 interferes in normal glucose metabolism by dysregulation of the tryptophan metabolism pathway are presented in this study. The literature review found an increased potential for alteration of normal glucose metabolism in viscose rayon occupational workers exposed to CS 2 . Occupational workers in the energy extraction industry exposed to CS 2 and other sulfide compounds may have an increased potential for glucose metabolism interference, which has been an indicator for diabetogenic effect and other related health impacts. The recommendation of this study is for implementation of regular monitoring of blood glucose levels in CS 2 -exposed populations as a preventative health measure.